Iloprost Duration for Digital Ulcers in Systemic Sclerosis: French Retrospective Study at Two Centers and Literature Review - Jamart, Céline; Levesque, Hervé; Thietart, Sara; Fain, Olivier; Rivière, Sébastien; Benhamou, Ygal; Mekinian, Arsène (Frontiers in Medicine, 2022)
Objective Ischemic digital ulcers (DUs) are frequent and severe complications of systemic sclerosis (SSc). Treatment options for SSc-related digital vasculopathy are based on aggressive vasodilation, with the objective to improve blood flow in ischemic areas. Intravenous prostanoids are recommended to treat active DUs. However, the level of evidence for the duration of 5 days is low. Therefore, the aim of this study was to determine whether prolonging the infusion beyond 5 days increases the rate of healing of active DUs in SSc. Methods This is an observational longitudinal retrospective bicenter study from 2000 to 2017. The objective was to compare the healing rate and time (defined by a healing of at least 50% of DUs) between two durations of iloprost administration: 5 days or less, or more than 5 days. Results Forty-one patients, with a mean age of 47 ± 15 years at diagnosis and 32 (78%) females have been included. Systemic sclerosis was diffuse in 10 (24%) cases and 13 (32%) had an interstitial lung disease. A total of 243 iloprost infusions for DUs were performed: 140 infusions for 5 days or less, and 103 infusions for more than 5 days (prolonged duration). Patients with active DUs which received >5 days of iloprost had higher modified Rodnan skin scale at the time of iloprost infusion (median 33 vs. 15; p < 0.05), more interstitial lung disease (44 vs. 27%; p < 0.05), more anti-topoisomerase I antibody positivity (59 vs. 44%; p < 0.05), and received more previous cyclophosphamide therapy (48 vs. 19%; p < 0.05). While the number of active DUs before iloprost infusion was not significantly different among those who received ≤5 days and >5 days of iloprost, the time to healing after iloprost infusion significantly decreased in SSc patients who received >5 days iloprost infusion: 48 [7–392] vs. 91 [9–365] days (p < 0.05). The proportion of SSc patients with healed DUs tended to increase in patients with >5 days iloprost infusion (log rank = 0.06). The number of patients with complete DU healing at day 90 was significantly increased in SSc who received >5 days of iloprost: 53 (51%) vs. 52 (37%) (p < 0.05). In addition, the time to healing was not significantly associated with the use of calcium channel blockers, endothelin receptor antagonists or a combination of PDE-5 inhibitors. Conclusion Prolonging duration of iloprost >5 days could improve the healing rate and the time to healing of SSc-related DUs. Prospective randomized studies are needed to confirm these data and define the optimal duration of iloprost therapy.